Synthesis of 4-Sulfanylcoumarins Using Thiourea and Alkyl Halides as the Sulfanylation Agent in Polyethylene Glycol–Water - Yin, Zhenlan; Wang, Yu; Yang, Qin; Wang, Ying; Xu, Jingshi; Deng, Zhihong; Peng, Yiyuan (Synthesis, 2013)
A novel and efficient route for the synthesis of 4-sulfanylcoumarins is disclosed. The direct sulfanylation of 4-tosyloxycoumarins with thiourea and various alkyl halides in polyethylene glycol 200–water (PEG 200–H2O), at room temperature under an air atmosphere, affords the corresponding 4-sulfanylcoumarins in moderate to excellent yields. This transformation shows good substrate scope and takes place in a green solvent.
Keywords: 4-sulfanylcoumarins; 4-tosyloxycoumarins; thiourea; alkyl halides; polyethylene glycol 200